2019
DOI: 10.15562/ism.v10i3.479
|View full text |Cite
|
Sign up to set email alerts
|

The level of knowledge and attitude towards dengue fever among medical students of Udayana University, Bali, Indonesia in 2018

Abstract: Background: There is a lot of impact of dengue among youngsters and also adults. The virus infects human blood and causes a migrainelike headache, rash, achiness, queasiness, tiredness and fever. Severe dengue can cause organ damage, severe bleeding, dehydration and even death. So, this study aims to know the level of knowledge and attitudes towards dengue infection among medical students from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Most samples in this study did not have an illness history of DHF in the past year; however, this area is categorized as endemic and had experienced an outbreak of DHF. Several studies have indicated that if a family member had suffered from DHF, there would be a lesson learned on a better anticipative attitude to conduct the prevention [39], [40]. Research results show that the illness history of DHF is not related to control measures of vector Aedes sp.…”
Section: Factors Associated With the Control Measures For Vector Aedes Sp Breeding Placesmentioning
confidence: 96%
“…Most samples in this study did not have an illness history of DHF in the past year; however, this area is categorized as endemic and had experienced an outbreak of DHF. Several studies have indicated that if a family member had suffered from DHF, there would be a lesson learned on a better anticipative attitude to conduct the prevention [39], [40]. Research results show that the illness history of DHF is not related to control measures of vector Aedes sp.…”
Section: Factors Associated With the Control Measures For Vector Aedes Sp Breeding Placesmentioning
confidence: 96%